PRODUCT BASED VALUE ADDED DALAM MENINGKATKAN COSTUMER DECISION DI INDOMARET KRAKSAAN - Mohammad Zainul Aripin; Achmad Febrianto (Jurnal Istiqro, 2022)
This study aims to analyze and understand the product-based value added strategy in improving customer decisions in a business towards consumer purchases in the research object at Indomaret retail, Kraksaan District. This study uses a qualitative approach, where the researcher tries to understand the phenomena that occur. Data collection techniques carried out in this study were carried out by observing, interviewing, and interviewing. Data analysis was carried out by presenting the data, and followed by drawing conclusions. The results showed that in product based value added in improving customer decision in Indomaret, Kraksaan District, it was done by determining the location of market intelligence, customer service, product of store and competitive price.